2008
DOI: 10.1016/j.otohns.2008.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Demagnetization of Cochlear Implants and Temperature Changes in 3.0T MRI Environment

Abstract: Patients carrying CIs with non-removable magnets should not enter a 3.0T MRI device in a routine clinical setup. Under special conditions (angle between the two magnets less than 80 degrees) imaging in a 3.0T MRI may be possible without harming the patient or the implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…Demagnetization is a potential problem which depends on the position of the magnet in relation to the magnetic field of the scanner (11). Implant displacement …”
Section: Discussionmentioning
confidence: 99%
“…Demagnetization is a potential problem which depends on the position of the magnet in relation to the magnetic field of the scanner (11). Implant displacement …”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies of normal human binaural processing have used magnetic resonance imaging of the inferior colliculus (Thompson et al, 2006), this technique is contraindicated for CI users (Majdani et al, 2008). Binaural interaction can also be studied using electrophysiology as shown in normal hearing individuals (Wada and Starr, 1989;Furst et al, 1990;Jiang and Tierney, 1996;Goksoy et al, 2005) as well as bilateral CI users (adults: He et al, 2010; children: Gordon et al, 2007a;cats: Smith and Delgutte, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cadaver studies have shown that the force required to fracture the CI receiver bed was much higher than that generated in a 1.5-T MRI scanner (7,8). Although demagnetization of the internal magnet is a concern, in practice this effect has been minimal even after multiple MR images (5,9,10), and the effect probably is only significant with 3-T scanners (11).…”
mentioning
confidence: 99%